GAMBARAN KARAKTERISTIK IBU HAMIL DENGAN PRE EKLAMPSI BERAT - Sibuea, Elizabeth Agustina (JURNAL MEDIA KESEHATAN, 2018)
Severe pre eclampsia (PEB) is a complication that is characterized by the onset of hypertension 160/110 mm Hg or more with proteinuria and or / edema at 20 weeks gestation or more. This study aims to describe the characteristics of pregnant women with PEB in the Rose Room RSUD dr. M. Yunus Bengkulu 2013. This study used a descriptive research method. The population in this study, all pregnant women with PEB, amounting to 238 people and sampling a total sampling. Secondary data were analyzed using univariate. The results of this study showed that almost half of pregnant women who experience PEB aged <20 years amounted to 109 persons (45.8%), almost half of pregnant women are primigravida numbering 111 people (46.6%), 238 pregnant mothers throughout the PEB experience with gestational age> 28 weeks, and almost half of pregnant women who experience PEB primary education amounted to 118 people (49.6%).